A new species and new distribution records for Braconidae from Mountain Lake Biological Station in southwestern Virginia and a redescription of Pentapleura foveolata Viereck - Kula, Robert R. (Zootaxa, 2013)
One new species of Alysiinae, Coelinius wrayi Kula, is described. Pentapleura foveolata Viereck, also in Alysiinae and previously known only from a male collected at the type locality in Connecticut, is redescribed based on six females and two males collected at Mountain Lake Biological Station (MLBS) in Virginia. Morphological variation for Alysia (Alysia) salebrosa Wharton is discussed given variation observed in specimens from MLBS. Sixty-two species of Braconidae col-lected at MLBS in August of 2009 are listed along with 12 species reported previously from MLBS. Host use for the 62 species is discussed; 31 are in Alysiinae or Opiinae, subfamilies that exclusively contain parasitoids of cyclorrhaphous flies. Fifteen species are reported from Virginia for the first time. Problematic couplets in a key to species of Spathius Nees for North America (Marsh & Strazanac 2009) are discussed using specimens from MLBS.